Social media – New challenges and approaches for communications research (Editorial) - Golding, Peter (2017)
This issue of the European Journal of Communication comprises revised versions of papers first given at a symposium convened and hosted by the journal, and held at the University of Minho, Braga, Portugal, in May 2016. We are extremely grateful to the University, and especially to the Centro de Estudos de Comunicação e Sociedade (Communication and Society Research Centre). The discussion prompted by the presentation of papers at the symposium allowed for the revision of the papers into their present form. The topic of social media has been a recurrent one in papers published or received by the Journal in recent years. Many such papers have derived from relatively small-scale research on the use of social media by homogeneous groups, or have taken a particular interest in the presumed ways in which such media have affected, even transformed, the nature of political communication, whether this means the methods by which politicians communicate with the electorate or by which political mobilisation among embryonic social movements is developed. It seemed to us essential to take stock of where much of this work is going, and of the assumptions that were often left unstated within it.